PENGARUH TEKANAN EKSTERNAL, FAKTOR POLITIK, ETIDAKPASTIAN LINGKUNGAN, KOMITMEN PIMPINAN, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAPPENERAPANTRANSPARANSI PELAPORAN KEUANGAN (Studi Empiris pada SKPD Kabupaten Kampar) - Ummi Umaroh; Desmiyawati '; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to provide empirical evidence of the influence of external pressures, political factors, the uncertainty of the environment, management commitment, and competence of human resources towards the implementation of the transparency of financial reporting (an empirical study on Kampar District).The sample in this studyusing a convenience sampling method.That SKPD in Kampar regency. Respondents involved in this research were 82 respondents consisting of Head of finance, treasurers, finance staff and Stylists Financial Officer. The technique of collecting data using questionnaires. The statistical method used to test the hypothesis is multiple regression with the help of SPSSversion 17.0.The results of this study provide evidence that partially or simultaneously variable external pressures, political factors, the uncertainty of the environment, and human resource competencies affect the implementation of the transparency of financial reporting. As for the variable leadership commitment partially negative effect on theimplementation of the transparency of financial statements. The magnitude of the effect of the independent variable on the dependent variable that is equal to 49.3%. while the remaining 31.7% is influenced by other variables not included in this study.Keywords:Pressure, Political, Environmental Uncertainty, Commitment, and Competence.